Investigating indigenous knowledge for sustainable livelihood in east coast, peninsular Malaysia - Che Soh, Mazlan; Omar, Siti Korota'aini (2011)
A Malay master craftsman design and produces his magnificent craft based on his excellent skill, knowledge, photographic memory and dedication. Today, these hand-made traditional crafts appear to fade into oblivion. The indigenous knowledge is fighting a losing battle with knowledge economy, a cohort of globalization. Indeed, globalisation has been knocking our doors long before the days of Parameswara in 1400's. The difference then and today is on the conduct of the visits. The merchants from the West Asia brought their religion, Islam and knowledge, together with their goods. Today, globalization enters ones home through cyber technology. It demolishes borders, redefines rules, creates new culture and challenges a sovereign political power. It constructs new markets and wealth as well as discontents. Globalization brought employment opportunities to the needy. Yet, multinational corporations, due to their aggressive promotion through the media have created new consumerist culture, screaming rock music, punks and ecstasy pills. The global economy, supported by globalization, changes the way the local population views their traditional livelihood and ways of life. Indigenous knowledge is facing extinction. Once a flourishing trade, traditional boatmaking and repair work is facing serious problems with regards to its sustainability. Foreign craftsmen from Thailand are flooding the job-market in Kelantan and Terengganu. The research attempts to address the issues on the existing situation on indigenous knowledge among the Malay communities, taking into example in both cases of keris making and boatbuilding in Kelantan and Terengganu. This research ascertained that: a) there is no effective mechanism of indigenous knowledge transfer within the community, which could be utilised to improve the quality of life of the population; b) the roles of the state, agencies and interest groups in building the indigenous knowledge and sustainable livelihood of the indigenous community are unclear; and c) There is limited opportunity for the members of the indigenous community to ascend into the economic mainstream and improve the quality of their lives through knowledge sharing and utilization.